Research on the ablation characteristics of combined lasers for glass fiber reinforced plastic composites - Xiao, Jing; Ren, Gang; Guo, Rongjun; Gan, Chunquan; Xu, Yongjun; Liu, Quanxi; Li, Shijie; Han, Dong; Lai, Gengxin (Frontiers in Physics, 2023)
Glass fiber reinforced plastic (GFRP) composites have been applied to the manufacture of missile shields and unmanned aerial vehicle (UAV) shells. It is of great significance to explore the ablation characteristics of different lasers for these composites. Currently, most existing studies on the ablation characteristics of lasers for Glass fiber reinforced plastic composites are conducted under a single laser output mode, such as continuous wave (CW) laser or pulsed laser. However, the ablation characteristics of combined lasers for Glass fiber reinforced plastic composites have not been clarified. Therefore, the ablation characteristics of single lasers (continuous wave, millisecond (ms) pulsed, or nanosecond (ns) pulsed laser) and combined laser (CW/ms or CW/ns combined pulsed lasers) were investigated by experimental and simulation methods in this study. Additionally, the ablation mechanisms of Glass fiber reinforced plastic under different laser irradiation conditions were compared and analyzed. The results demonstrated that the ablation rates of single lasers for Glass fiber reinforced plastic composites were all within an order of magnitude of 10 μg/J, which was not significantly correlated with the light source system. The ablation efficiency of the single laser was determined by the incident laser energy. The continuous wave laser was found to be the optimal light source for the ablation and destruction of Glass fiber reinforced plastic composites. Nevertheless, there were some obstacles in the ablation process of continuous wave lasers. Applying pulsed lasers during the irradiation of the continuous wave laser may generate a synergistic effect. Under the conditions in this study, the CW/ns pulsed combined laser increased the ablation efficiency by 53.8%.